2015
DOI: 10.2169/internalmedicine.54.3161
|View full text |Cite
|
Sign up to set email alerts
|

Breath Sound Intensity during Tidal Breathing in COPD Patients

Abstract: Objective There is a discrepancy in the intensity of breath sounds in chronic obstructive pulmonary disease (COPD) patients between subjective studies, which have reported a diminished intensity, and objective studies using airflow-standardized measurements, which have not demonstrated a diminished intensity. We herein evaluated the breath sound intensity in COPD patients during tidal breathing in order to obtain clinically relevant results. Methods The subjects included 20 stable COPD patients and 20 normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In our analysis, there were significant differences in age and sex between the healthy and bronchial asthmatic populations. Lung sound data from the healthy volunteers presented in this article were previously published11 and did not include immunoglobulin E data. However, these factors may not have had an impact on these results, as previous data from our laboratory suggested that sex and age do not affect the E/I LF or E/I MF values7,8 and the primary outcomes of this study were evidently clarified by the asthmatic subject data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our analysis, there were significant differences in age and sex between the healthy and bronchial asthmatic populations. Lung sound data from the healthy volunteers presented in this article were previously published11 and did not include immunoglobulin E data. However, these factors may not have had an impact on these results, as previous data from our laboratory suggested that sex and age do not affect the E/I LF or E/I MF values7,8 and the primary outcomes of this study were evidently clarified by the asthmatic subject data.…”
Section: Discussionmentioning
confidence: 99%
“…Lung sound data from the 20 healthy volunteers presented in this article were previously published 11. All asthmatic subjects who first visited our hospital from September 2011 to November 2014 included in this study fulfilled the Global Initiative for Asthma criteria 10.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are many investigations regarding lung sound amplitude, transmission, distribution, or adventitious sounds [3,4,5,6,7,10,12,14,20,21], there are only a few reports to study lung sound asynchrony [8,9,13,15]. Wang et al [9] revealed that asynchrony between the left and right lung in asthma exacerbations was significantly reduced after clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Auscultation of respiratory sounds has long been an important physical assessment technique for medical workers [1], and with the influx of recent technology, auscultated respiratory sounds for pneumonia [2], bronchial asthma [3], and sleep apnea syndrome [4] are being used for chronic obstructive pulmonary disease (CODP) [5,6] diagnosis, tidal volume estimation [7], snoring detection [8], and apnea detection [9]. Moreover, respiratory rate monitoring using respiratory sounds [10] and snoring sensors [11] has become plausible due to unique advantages such as being a non-invasive technique and being based on low-cost, high-performance microphones that readily available in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, respiratory rate monitoring using respiratory sounds [10] and snoring sensors [11] has become plausible due to unique advantages such as being a non-invasive technique and being based on low-cost, high-performance microphones that readily available in the market. Although the above-mentioned methods using respiratory sounds have been extensively studied via signal processing [3][4][5][6][7][8][9], the outcomes of these analyses have not often been practically implemented.…”
Section: Introductionmentioning
confidence: 99%